Analisis Kritis Fenomena Cancel Culture dan Ancaman terhadap Kebebasan Berekspresi: Critical Analysis of Cancel Culture Phenomena and Threats to Freedom of Expression - Juniman, Puput Tripeni (Al-Adabiya: Jurnal Kebudayaan dan Keagamaan, 2023)
The digital platform grows rapidly and is no less important than the physical realm where people building all life necessities in both realms. In addition, the internet and social media are also places for voice and expression. In the midst of freedom of expression in the digital world, a new phenomenon known as the cancel culture, has emerged. This culture makes people, organizations and products rejected in the online presence which has also affected their phyisical reality. A massive cancellation culture can destroy a person's reputation and are often no longer accepted in both digital and real world. This study aims to analyze the impact of the culture on freedom of expression. This study departs from the philosophical framework of ontology, epistemology, axiology and the theory of freedom of expression developed by Thomas Scanlon. Employing a qualitative approach as well as a critical discussion of the topic being carried out, data was collected through literature studies from various journal articles and online news regarding cancel culture and freedom of expression. The results of the analysis show that cancel culture can threaten freedom of expression in both phyisical and digital realms.